Psychosocial working conditions and wellbeing in contract workers in higher education in Singapore - Tan, Charissa (2024)
There is a growing trend within many sectors, such as higher education institutes (HEI), to utilise contract workers (McComb et al., 2021). Consequently, this type of employment contract has become more prevalent within the workforce (Lahiri & Schwartz, 2018). Contract workers (also known as fixed-term contract workers) refer to employees whose employment will terminate on the expiry of a specific term unless it is renewed. As flexible employment contracts become more prevalent in organisations and HEIs, understanding the psychosocial working conditions faced by contract workers is important to protect their work-related wellbeing and mental health. However, these working conditions are not well understood as majority of research in this area has focused on traditional, permanent workers. This population, considered “hard-to-reach” by researchers (e.g., Ellis, 2021), has important contextual experiences that could further our understanding of the antecedents and mechanisms explaining wellbeing in contract workers.